Complex phenotypes in mosquitoes and mice associated with neutralization escape of a Dengue virus type 1 monoclonal antibody - Shrestha, Bimmi (2012)
DENV1-E106 is a monoclonal antibody (MAb) with strong neutralizing activity against all five DENV-1 genotypes and therapeutic activity in mice. Here, we evaluated the potential for DENV-1 to escape neutralization by DENV1-E106. A single mutation in domain III of the envelope protein (T329A) emerged, which conferred resistance to DENV1-E106. However, the T329A variant virus had differing phenotypes in vitro and in vivo with attenuation in cell culture yet increased infectivity in Aedes aegypti mosquitoes. Mice infected with this T329A variant still were protected against lethal infection by DENV1-E106 even though much of the neutralizing activity was lost. This study reveals the complex dynamics of neutralization escape of an inhibitory MAb against DENV, and suggests that evaluation of therapeutic MAbs requires detailed investigation in relevant hosts.